Features of intellectual capital management at the enterprise - Amirbekuly, Ye.; Aimukhanbetova, G. (BUKETOV BUSINESS REVIEW, 2018)
The article deals with the management of intellectual capital of the enterprise that is a set of intellectual resources, skills that a person uses for getting profit. Various approaches to the understanding of the management of intellectual capital, and the principles and approaches to building intellectual capital management systems are considered. The principles of human resource management, which are based on scientific, integrated and systemic approaches, are considered. The authors unrevealed the basic principles of the intellectual capital management system, which allow solving the main problems arising in the process of managing intellectual capital at an enterprise. The authors have considered a subsystem of intellectual capital management, which stands out along with financial, productive and other sub systems of enterprise management. The need of organization of developed network is show non which will circulate information within the organization. The chain «information - knowledge - intellectual product - intellectual capital» is highlighted, which management will enhance the effectiveness of both individual units and the entire intellectual capital of the enterprise. The interrelation of the intellectual capital of the enterprise with its innovative activity is considered; recommendations on the analysis of the internal environment of enterprise with the viewpoint of innovative potential are offered.